Pengembangan Internet Of Things pada Smart City - Agung Ahmad (Jurnal Sistem Cerdas, 2018)
Smart city is an advanced urban area that excels in the fields of economy, government, people and life through strong human capital, social capital and ICT infrastructure. This is a new approach to managing the complexity of city life, increasing efficiency, reducing costs and improving the quality of life of citizens. This paper is about potential smart city applications as applied to the domains of intelligent transportation, intelligent tourism and recreation, smart health, ambient assistance, crime prevention and community safety, governance, monitoring and infrastructure, disaster management, environmental management, garbage collection and sewer management, smart homes, and smart energy. This smart city application supports the vision of the future of cities, which aims to exploit ICTs, namely the internet of things technologies (IoT), for the provision of value-added services. Furthermore, this paper presents technical solutions for energy control and comfort at home for proof of the concept of smart city infrastructure applications. The demonstration described here is about how smart applications can manage energy and comfort control in a room that has a number of people and electrical equipment, with each being a source of heat.